2015
DOI: 10.1002/jcu.22320
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fetal sex determination on ultrasound examination in the first trimester of pregnancy

Abstract: The sex of a fetus can be accurately determined on sonographic examination in the first trimester of pregnancy; the accuracy of this prediction is influenced by the fetal CRL and GA and by the maternal body mass index. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44:272-277, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…However, pregnant women are increasingly requesting sex determination at a first‐trimester ultrasound (eg, 12 weeks' gestation), despite the lower accuracy of sex determination at this gestation . One 2016 study found that from the gestational age of 12 weeks, fetal sex determination was both feasible and accurate in 79% of cases; there is increased sensitivity in the determination of female sex compared with male sex . With increased gestational age (eg, beyond 14 wk), fetal sex determination becomes significantly more accurate than at 12 weeks' gestation …”
Section: Current Methods Of Sex‐selective Termination Of Pregnancymentioning
confidence: 99%
“…However, pregnant women are increasingly requesting sex determination at a first‐trimester ultrasound (eg, 12 weeks' gestation), despite the lower accuracy of sex determination at this gestation . One 2016 study found that from the gestational age of 12 weeks, fetal sex determination was both feasible and accurate in 79% of cases; there is increased sensitivity in the determination of female sex compared with male sex . With increased gestational age (eg, beyond 14 wk), fetal sex determination becomes significantly more accurate than at 12 weeks' gestation …”
Section: Current Methods Of Sex‐selective Termination Of Pregnancymentioning
confidence: 99%
“…50 The reported accuracy of fetal sex determination in the modern era with universal first trimester transvaginal ultrasound is approximately 70% at 11w, 97% at 12w, and 100% at 13w. 58,[61][62][63] Accuracy improves with advancing gestational age, experience, the use of transvaginal imaging and 3D ultrasound after 12 weeks (Figure 3). [61][62][63][64] Fetal sex assignment in second and third trimester ultrasound What's already known about this topic?…”
Section: Ultrasoundmentioning
confidence: 99%
“…Ultrasonography: Prediction of the fetal sex by ultrasonography is based on the assessment of the external genitalia. Among humans it is safe and cost-effective and was shown lately to be accurate even in the first trimester [56]. It is successfully used in animals including horses [57], cows [58], and other large animals.…”
Section: Physical (Anatomical) Examinationmentioning
confidence: 99%